Identification of Key Agility Variables to Improve Poultry Supply Chain Sustainability: Indonesian Case - Yunita, Ika; Hasibuan, Sawarni; Thaheer, Hermawan (Department of Agro-industrial Technology, University of Brawijaya, 2022)
AbstractAll industries face new challenges after COVID-19, including the Indonesian poultry industry. As an essential food supply sector, the poultry industry supply chain must respond and adapt to new post- COVID-19 conditions. This study aims to analyze the relationship between agility and sustainability in the supply chain of the Indonesian poultry industry for facing various challenges. The method used in this research was the Interpretive Structural Modeling-“Matriced Impacts Croisés Appliquée á un Classement” (ISM-MICMAC) method. The agility and sustainability variables were validated initially by involving industrial supply chain stakeholders in the Focus Group Discussion (FGD). The study successfully modeled the relationship between agility and sustainability in the integrated supply chain of the Indonesian poultry industry. The agility variable is the driver for the sustainability of the integrated national poultry industry supply chain, with customer sensitivity being an essential key factor in improving the sustainability of the Indonesian poultry supply chain.Keywords: COVID-19, agility, sustainability, ISM-MICMAC AbstractSemua industri menghadapi tantangan baru pasca COVID-19, termasuk industri unggas nasional. Rantai pasok industri unggas sebagai sektor penting untuk pasokan makanan harus mampu merespon dan beradaptasi dengan kondisi baru pasca COVID-19. Penelitian ini bertujuan untuk menganalisis hubungan antara kecepatan berpindah dan keberlanjutan pada rantai pasok industri unggas nasional dalam menghadapi berbagai tantangan. Metode yang digunakan adalah metode Interpretive Structural Modeling-Matriced Impacts Croisés Appliquée á un Classement (ISM-MICMAC). Validasi terhadap variabel kecepatan berpindah dan keberlanjutan dilakukan pada tahap awal dengan melibatkan aktor rantai pasok industri pada forum Focus Group Discussion (FGD). Hasil penelitian berupa model hubungan antara kecepatan berpindah dan keberlanjutan pada rantai pasok industri unggas nasional terintegrasi. Variabel kecepatan berpindah menjadi pendorong keberlangsungan rantai pasok industri unggas nasional yang terintegrasi dengan customer sensitivity menjadi faktor kunci yang penting untuk meningkatkan keberlanjutan rantai pasok industri unggas.Kata kunci: COVID-19, ISM-MICMAC, keberlanjutan, kecepatan berpindah